Dual-Band Circularly Polarized Dielectric Resonator Antenna for WLAN and WiMAX Applications - Amir Altaf; Munkyo Seo (Sensors, 2020)
In this paper, a new dual-band circularly polarized (CP) dielectric resonator antenna for WLAN and WiMAX applications is proposed. The dielectric resonator has an asymmetric Y-shaped geometry. By properly selecting the length of the arms, the pairs of fundamental (TE <semantics> 111 </semantics> ) and second-order (TE <semantics> 211 </semantics> ) are excited separately at the design frequencies to radiate the CP wave. The measurement shows that the fabricated antenna exhibits a wide impedance bandwidth for |S <semantics> 11 | < </semantics> −10 dB of 62.07% (2.2−4.18 GHz). The far-field measurements in the broadside direction demonstrated a dual-band CP response with 3 dB ARBWs of 4.92%(2.38−2.5 GHz) at the lower and 12.64% (3.26−3.70 GHz) at the upper band. The measured CP bands cover the entire frequency range of WLAN (2.401−2.495 GHz) and WiMAX (3.4−3.69 GHz) at the lower and upper bands, respectively.